Correlates of tuberculosis and non-tuberculosis morbidity and immunity in sub-Saharan African HIV-exposed, uninfected infants - Iwase, Saori Christina (Department of Clinical Laboratory Sciences, 2025)
Background: Perinatal HIV transmission has been considerably reduced due to successful intervention programs. Consequently, there is a growing population of infants who are HIV-exposed but uninfected (iHEU), particularly in sub-Saharan Africa. These infants experience an increased risk of morbidity compared to infants who are HIV-unexposed and uninfected (iHUU), predominantly due to infectious diseases. Although the mechanisms underlying this increased vulnerability remain unclear, it may be associated with their altered immunity and/or gut microbiota. Bacillus Calmette-Guérin (BCG) vaccination is an effective intervention to prevent severe tuberculosis (TB) disease in children. BCG vaccination also enhances heterologous protective immunity against infections through epigenetic reprogramming of innate immune cells (known as “trained innate immunity”). However, whether iHEU receive comparable protection from BCG induced immunity against TB and non-TB infection as iHUU remains elusive. Gut microbiota plays a critical role in immune development during infancy. A close relationship between gut microbiota and vaccine responses has been reported in iHUU, including tetanus toxoid (TT) vaccination. However, a limited number of studies longitudinally investigated the effect of in utero HIV exposure on the gut microbiota, and results are often conflicting. In addition, not many studies have compared the trajectory of gut microbiota between iHEU and iHUU across multiple countries. While several studies have indicated reduced immune responses against TT vaccination in iHEU compared to iHUU, the interplay between HIV exposure, gut microbiota, and vaccine response is largely unexplored. Aims: In this dissertation, we examined three potential contributing factors that may underlie the higher risk of morbidity observed among iHEU in sub-Saharan Africa. The specific aims were to examine whether BCG affords the same protection against TB infection (TBI) and disease in iHEU (corresponds to Aim 1), effect of HIV exposure on longitudinal gut microbiota composition and its association with TT vaccine response (corresponds to Aim 2), and optimization of epigenetic assay protocol, intended for future investigation of BCG-induced histone modifications in iHEU (corresponds to Aim 3). Methods and results: To assess TBI prevalence among iHEU and iHUU, a total of 418 mother-infant pairs from South Africa and Botswana were included. All infants received BCG vaccination at birth as per standard of care. T-SPOT.TB (ELISpot-based interferon-gamma release assay) was performed using cryopreserved peripheral blood mononuclear cells (PBMCs) from infants aged 9-18 months. The prevalence of TBI did not differ by the infant HIV exposure status, with 10 cases (3.4%) among iHEU and four cases (3.2%) among iHUU, none with symptoms of active TB disease. This trend was the same across two different African countries where the burden of HIV and TB is high. However, because of the lower T-SPOT.TB positivity than initially anticipated, we were under powered to conclude the effect. To assess whether gut microbial succession alters immunity in iHEU, we profiled longitudinal gut microbiota composition and associated this with TT vaccine responses in 354 mother-infant pairs from South Africa and Nigeria. Stool samples were collected at 1 and 15 weeks of life, and 16S ribosomal ribonucleic acid (rRNA) gene sequencing was performed. Plasma IgG anti-tetanus antibody titers were measured by enzyme-linked immunosorbent assay (ELISA). The effect of HIV exposure on infant gut microbiota composition was relatively modest compared to the impact of age and geographical factors. However, HIV exposure and specific gut microbes were independently associated with the TT vaccine response at 15 weeks of age. Results for South Africa and Nigeria differed, possibly due to higher maternal anti-tetanus IgG titers and hence infant baseline titers in Nigeria. To optimize an epigenetic assay that can be applied to infant samples, monocytes and natural killer (NK) cells were isolated from cryopreserved PBMCs using fluorescence-activated cell sorting (FACS). Cleavage Under Targets and Tagmentation (CUT&Tag) was optimized for assessing the histone modifications, acetylation of histone H3 at lysine 27 (H3K27Ac), trimethylation of histone H3 at lysine 4 (H3K4me3), and trimethylation of histone H3 at lysine 27 (H3K27me3; also used as a positive control). The optimized protocol was then applied to a subset of infant samples (n = 14; aged between six and seven weeks). Optimal input cell number, polymerase chain reaction (PCR) cycles, and sequencing depth were carefully determined for the CUT&Tag assay. These adjustments were necessary to achieve the assay's feasibility and data quality. The optimized CUT&Tag protocol and fine-tuned data analysis strategy successfully exhibited its capability to analyze multiple histone modifications using only 5,000 infant monocytes or NK cells as an input sample. Conclusions: Prenatal HIV exposure and gut microbiota may independently influence infant TT vaccine response. This supports the existing notion that iHEU exhibit altered immunity. Although previous studies have indicated that iHEU experience a higher risk of infection than iHUU, our data suggested that BCG vaccination was equally protective against TBI, irrespective of HIV exposure status. The optimized CUT&Tag protocol will offer a useful tool for investigating histone modifications using ultra-low input samples. This will be employed in the future study to explore whether iHEU exhibit comparable epigenetic modifications induced by BCG vaccination as for iHUU, providing valuable insight into whether iHEU receive similar non-specific protection from BCG vaccination compared to iHUU.